SKP alleviates the ferroptosis in diabetic kidney disease through suppression of HIF-1α/HO-1 pathway based on network pharmacology analysis and experimental validation - Yangtian Yan; Ningning Yuan; Yuchi Chen; Yun Ma; Ali Chen; Fujing Wang; Shihua Yan; Zhuo'en He; Jinyue He; Chi Zhang; Hao Wang; Mingqing Wang; et al. (BMC, 2024)
Abstract Background Diabetic kidney disease (DKD) represents a microvascular complication of diabetes mellitus. Shenkang Pills (SKP), a traditional Chinese medicine formula, has been widely used in the treatment of DKD and has obvious antioxidant effect. Ferroptosis, a novel mode of cell death due to iron overload, has been shown to be associated with DKD. Nevertheless, the precise effects and underlying mechanisms of SKP on ferroptosis in diabetic kidney disease remain unclear. Methods The active components of SKP were retrieved from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Protein-protein interaction (PPI) network and Herb-ingredient-targets gene network were constructed using Cytoscape. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted utilizing the Metascape system database. Additionally, an in vivo model of DKD induced by Streptozotocin (STZ) was established to further investigate and validate the possible mechanisms underlying the effectiveness of SKP. Results We retrieved 56 compounds and identified 223 targets of SKP through the TCMSP database. Key targets were ascertained using PPI network analysis. By constructing a Herb-Ingredient-Targets gene network, we isolated the primary active components in SKP that potentially counteract ferroptosis in diabetic kidney disease. KEGG pathway enrichment analysis suggested that SKP has the potential to alleviate ferroptosis through HIF signaling pathway, thereby mitigating renal injury in DKD. In animal experiments, fasting blood glucose, 24 h urine protein, urea nitrogen and serum creatine were measured. The results showed that SKP could improve DKD. Results from animal experiments were also confirmed the efficacy of SKP in alleviating renal fibrosis, oxidative stress and ferroptosis in DKD mice. These effects were accompanied by the significant reductions in renal tissue expression of HIF-1α and HO-1 proteins. The mRNA and immunohistochemistry results were the same as above. Conclusions SKP potentially mitigating renal injury in DKD by subduing ferroptosis through the intricacies of the HIF-1α/HO-1 signaling pathway.